Managing the Adoption of Geospatial Information and Technologies in Multiple Industries - Mohamad Rohieszan bin Ramdan (Tanjung Malim, 2024)
Managing the Adoption of Geospatial Information and Technologies in Multiple Industries by Mohamad Rohieszan bin Ramdan